Dynamics of Sadangserang Market and Terminal Relocation in the Perspective of Sustainable Planning - Winarni, Aris Toening (Universitas Pendidikan Ganesha, 2025)
The construction of modest flats (Rusunawa) in Sadangserang, Bandung City, is planned to use land currently used by the Sadangserang market and station. The temporary relocation of the market and station has the potential to trigger social conflict among traders, public transportation drivers, and the local community. This research is proposed to analyze the potential for social conflict from the perspective of sustainable development planning. The study was conducted using qualitative methods through in-depth interviews with key informants. The research results indicated that the potential for conflict arises from uncertainty about compensation and economic impacts for traders and terminal workers, as well as the loss of cultural identity and access to transportation for the community. Applying sustainable planning principles reduced the potential for conflict through fair compensation schemes, adaptation assistance, participation of affected groups, guaranteed rights to return to their original location, and cross-sectoral communication and coordination. This Research enriches the literature on urban informal infrastructure relocation studies with a perspective of sustainable planning. The research results are in the form of a reference for the government in formulating fair and sustainable relocation policies.